TO THE NOTES ON THE KEY ELEMENTS OF THE SUPPLY CHAIN AND THE SPHERES OF LOGISTIC SOLUTIONS FOR THEIR MANAGEMENT: TO THE NOTES ON THE KEY ELEMENTS OF THE SUPPLY CHAIN AND THE SPHERES OF LOGISTIC SOLUTIONS FOR THEIR MANAGEMENT - Stoyanov, Svetlozar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The research presents a short reference review of the key elements of the supply chain as characteristics of establishments and the spheres of logistic solutions for their management.